2010
DOI: 10.1111/j.1600-0609.2010.01549.x
|View full text |Cite
|
Sign up to set email alerts
|

T-type calcium channel as a portal of iron uptake into cardiomyocytes of beta-thalassemic mice

Abstract: Our findings indicated that iron uptake mechanisms in cultured thalassemic cardiomyocytes are mainly mediated by TTCC, suggesting that TTCC is the important pathway for iron uptake in this cultured thalassemic cardiomyocyte model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
90
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 83 publications
(95 citation statements)
references
References 39 publications
(76 reference statements)
5
90
0
Order By: Relevance
“…Studies on cultured cardiomyocytes of heterozygous (Hbb th-3 /Hbb þ ) b-thalassemic mice showed that treatment with a T-type calcium channel (TTCC) blocker and an iron chelator could prevent Fe 2þ uptake into cardiomyocytes, whereas blockers of transferrin receptor1 (TfR1), divalent metal transporter1 (DMT1) and L-type calcium channel (LTCC) could not. 18 However, blockers of TfR1, DMT1, LTCC and TTCC could not prevent Fe 3þ uptake into these cells. 17 These findings suggest that TTCC is an important pathway for Fe 2þ uptake in a cultured thalassemic cardiomyocyte model.…”
Section: /Hbbmentioning
confidence: 97%
See 2 more Smart Citations
“…Studies on cultured cardiomyocytes of heterozygous (Hbb th-3 /Hbb þ ) b-thalassemic mice showed that treatment with a T-type calcium channel (TTCC) blocker and an iron chelator could prevent Fe 2þ uptake into cardiomyocytes, whereas blockers of transferrin receptor1 (TfR1), divalent metal transporter1 (DMT1) and L-type calcium channel (LTCC) could not. 18 However, blockers of TfR1, DMT1, LTCC and TTCC could not prevent Fe 3þ uptake into these cells. 17 These findings suggest that TTCC is an important pathway for Fe 2þ uptake in a cultured thalassemic cardiomyocyte model.…”
Section: /Hbbmentioning
confidence: 97%
“…37 Both in vitro and in vivo studies indicated that heterozygous (Hbb th-3 /Hbb þ ) b-thalassemic mice were anemic, had increased heart weight and cardiac iron accumulation when getting old, and had measurable cardiac dysfunction. [13][14][15][16][17][18][19]30,32,33,[37][38][39][40] Moreover, the homozygous (Hbb th1 / Hbb th1 ), (Hbb d3(th) /Hbb d3(th) ) and heterozygous b-thalassemic mice showed a greater severity of anemia and had higher levels of cardiac iron accumulation than the heterozygous (Hbb th-3 /Hbb þ ) b-thalassemic mice did, even though the mice were still young. [37][38][39] A summary of reports regarding cardiac iron accumulation, cardiac function, and mitochondrial function in b-thalassemic mice (in vivo models) is shown in Table 2.…”
Section: The Hearts Of B-thalassemic Micementioning
confidence: 99%
See 1 more Smart Citation
“…Possibilities include L-type Ca 2+ channels, 42 T-type Ca 2+ channels, 43 or perhaps ZIP8, an iron and zinc transporter 39 that was reported to be up-regulated in heart tissue of thalassemic mice. 43 The lack of an effect of iron overload on heart ZIP14 levels might be due to heart-specific regulation or to the comparatively minor degree of iron loading in this tissue. The continued expression of ZIP14 during iron overload suggests that it was at least present to participate in NTBI uptake.…”
mentioning
confidence: 99%
“…Other studies have found that cardiac DMT1 levels were lower in iron-loaded animals than in controls. 44 Recently, Kumfu et al 43 reported that NTBI uptake by cardiomyocytes was unaffected when the iron uptake activity of DMT1 or TfR1 was blocked, indicating that DMT1 and TfR1 are not required for NTBI uptake into these cells. In iron-deficient heart, DMT1 levels were up-regulated 4-fold whereas ZIP14 levels were not affected.…”
mentioning
confidence: 99%